KESESUAIAN MATERI BUKU DEUTSCH ECHT EINFACH A1.1 DENGAN KURIKULUM 2013 KETERAMPILAN MEMBACA KELAS X SEMESTER 1 - Izzati, Zahrah Nurul; Pujosusanto, Ari (LATERNE, 2022)
Reading is the first receptive skill taught in language learning before productive skills. Therefore, reading is the first skill to be emphasized in learning a language, mainly German. In learning German, teaching materials are needed to support learning. One form of teaching material is a textbook. The Deutsch Echt Einfach book is one of the textbooks that can be used in learning German. The Deutsch Echt Einfach book is the latest book that has advantages, combining the learning material section (Kursbuch) and the practice section (Arbeitsbuch) in one book. This can make it easier for students to practice reading skills by applying the results of reading material (Kursbuch) in the practice section (Arbeitsbuch) in the same book to be more efficient. The material in the textbook should be in accordance with the curriculum. The formulation of the problem in writing this scientific article is whether the material in the Deutsch Echt Einfach A1.1 Lektion 1 and Lektion 2 books is following the 2013 curriculum by paying attention to the aspects of the material with basic competencies and the primary material in the 2013 curriculum syllabus in German class X semester 1. Writing This scientific article aims to describe the results of the analysis of the suitability of the Deutsch Echt Einfach A1.1 book with the German language curriculum class X semester 1. This scientific article study applies a qualitative approach with literature study techniques and data analysis using the Miles and Huberman model. The results of the analysis show that all dialogue texts and descriptive texts in Lektion 1 and Lektion 2 are following the 2013 curriculum criteria for reading skills for class X semester 1